Rethinking Mobile Food Safety: A Strategic Framework for Ambulant Vendors in the Philippines - Armas, Kenneth L.; Villegas, Marivic N.; Lopez, May Nerissa S.; La Penia, Rhea Lyn F. (International Review of Management and Marketing, 2024)
This research aims to assess the quality, safety, and hygienic practices of street vendors in San Isidro, Nueva Ecija. The study used a descriptive methodology, using a standardized questionnaire, interviews, and observations for data collection. 37 out of 41 companies in Poblacion, San Isidro, took part in the research. The sample size was determined using Sloven's Formula, and participants were chosen by purposive sampling. The data analysis included creating frequency distributions and calculating metrics of central tendency. The survey showed that most participants were female, married, and had finished high school. Most vendors were stationary, had been in business for less than five years, employed tricycles for promotion, and operated without any personnel. Commonly sold food items were siomai, siopao, kikiam, fishball, kwek-kwek, tokwa, nuggets, and tokneneng. Vendors usually bought items at the Public Market and then processed them on the premises. The commodities were displayed on open stands without shelter from heat, dust, or wind. The sanitary conditions were insufficient, lacking sufficient access to clean water and handwashing facilities. The stalls were situated far away from garbage cans, sewers, and toilets. Vendors routinely washed their hands before food preparation and delivery, but they did not consistently use aprons, hairnets, or gloves. Respondents exhibited diverse personal hygiene behaviors while cooking. Although most street food sellers provided trash bins, the separation of biodegradable and non-biodegradable garbage was not a widespread practice. Moreover, several merchants did not possess permits, knowledge of current rules, or compliance with sanitary regulations. Street retailers had difficulties due to external competition. Interventions are necessary to enhance the quality, safety, and hygienic practices of street vendors in San Isidro, Nueva Ecija based on these results. This information may be used by policymakers and local authorities to create and implement policies that support food safety and cleanliness in street selling.